Pax6 regulates neuronal migration and cell proliferation via interacting with Wnt3a during cortical development - Bichao Zhang; Meihua Hou; Jiayan Huang; Yunfei Liu; Ciqing Yang; Juntang Lin (Scientific Reports)
Abstract The paired box 6 (Pax6) gene encodes a highly conserved transcription factor, involved in the development of eyes, brain, and endocrine glands. Homozygous loss of Pax6 resulted in neonatal death in mice, plus loss of eyes and malformation of cerebral cortex. In patients with heterozygous Pax6 mutations, a reduction in thickness of the frontoparietal cortex was detected, which was also observed in small eye mice. In this study, we found that Pax6 overexpression increased the cortical thickness, especially in the intermediate zone of the cortex, which conflicts with the report of Manuel et al. Pax6 overexpression appears to detain neurons in the intermediate zone while promoting cell proliferation. It is worth noting that the impact of Pax6 overexpression on cortical thickness and neuronal migration was temporal, explaining the differences with other reports. We postulated that the alteration of Pax6 isoform ratio by autoregulation might be responsible for this. JASPAR analysis together with the results of qPCR, Western blot, CUT&Tag, and rescue experiments revealed that Pax6 regulates neuronal migration and cell proliferation by indirectly mediating Wnt3a expression. Therefore, we propose that Pax6 participates in corticogenesis via interaction with Wnt3a in regulating neuronal migration and cell proliferation.